1999
DOI: 10.1161/01.hyp.33.3.850
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II Receptor Blockade in Normotensive Subjects

Abstract: Abstract-Use of angiotensin (Ang) II AT 1 receptor antagonists for treatment of hypertension is rapidly increasing, yet direct comparisons of the relative efficacy of antagonists to block the renin-angiotensin system in humans are lacking. In this study, the Ang II receptor blockade induced by the recommended starting dose of 3 antagonists was evaluated in normotensive subjects in a double-blind, placebo-controlled, randomized, 4-way crossover study. At 1-week intervals, 12 subjects received a single dose of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(5 citation statements)
references
References 23 publications
0
4
0
1
Order By: Relevance
“…Irbesartan has the ability to inhibit the pressor response to exogenously administered angiotensin II in normotensive subjects and had a dose-related BP response as shown in several studies 39–41. Irbesartan inhibited the pressor response by up to 100% at peak after 4 hours of oral doses at 25–300 mg 40,41.…”
Section: Pharmacokinetics and Pharmacodynamicsmentioning
confidence: 89%
See 1 more Smart Citation
“…Irbesartan has the ability to inhibit the pressor response to exogenously administered angiotensin II in normotensive subjects and had a dose-related BP response as shown in several studies 39–41. Irbesartan inhibited the pressor response by up to 100% at peak after 4 hours of oral doses at 25–300 mg 40,41.…”
Section: Pharmacokinetics and Pharmacodynamicsmentioning
confidence: 89%
“…Irbesartan inhibited the pressor response by up to 100% at peak after 4 hours of oral doses at 25–300 mg 40,41. Compared with losartan and valsartan in a double-blind, placebo-controlled, randomized, four-way crossover study, the degree and duration of angiotensin II receptor blockade induced by 150 mg of irbesartan was significantly greater than with either 50 mg of losartan or 80 mg of valsartan 39. Furthermore, in studies evaluating its efficacy in hypertensive patients, chronic doses of up to 300 mg had no effect of clinical importance on renal plasma flow, glomerular filtration rate, filtration fraction, or urinary excretion of sodium and potassium 4244.…”
Section: Pharmacokinetics and Pharmacodynamicsmentioning
confidence: 95%
“…In addition to their effect on blood pressure, long-term administration of AT1 receptor blockers results in a several-fold increase in plasma ANG II and thus a possible overstimulation of AT2 receptors [40,41,42,43]. Therefore, the effect of AT2 receptor stimulation is becoming increasingly important in both physiological and pathological situations, for example, hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…In their experience on normotensive healthy volunteers, Mazzolai et al [29] found that oral administration of losartan 50 mg provides only 35 to 45% blockade of AT 1 receptors. This is consistent with findings from Maillard et al [30], who reported on the effects of losartan, valsartan, and candesartan dosing on AT 1 receptor blockade.…”
Section: Magnitude Of Ras Blockadementioning
confidence: 99%